Android Application for Testing English Proficiency - Nurindah Dwiyani; Yasdinul Huda (Jurnal Teknologi Informasi dan Pendidikan, 2023)
English, the official language of many states and international organizations, serves as the standard for instruction globally. English proficiency is another prerequisite from some employers for employment in the working world. To determine a person's level of English proficiency, the TOEIC exam is employed. Several companies use a candidate's TOEIC score as a proxy for their level of English ability. A series of assessments, including listening and reading tests, make up the TOEIC. It is imperative for someone to conduct independent study in order to improve their TOEIC score given the comparatively expensive cost of the TOEIC course and exam. The layout of this TOEIC test simulation application makes it simple to practice whenever you want, wherever because it can be utilized offline on a smartphone. The TOEIC test simulation application, which contains four main menus: tips and tricks, TOEIC simulation, solutions, and about, was made using the Eclipse editor and Java programming. The questions under the tips and tricks section can be answered in a snap using easy methods. The right or wrong answers to the exam questions that are shown in the simulation menu can be found by selecting the solution option.